Emotional processing during the therapy for complicated grief. (4th July 2022) - Pinheiro, Patrícia; Gonçalves, Miguel M.; Nogueira, Daniela; Pereira, Rui; Basto, Isabel; Alves, Daniela; Salgado, João
Abstract: Objective: Prior research, mainly conducted on depression, observed that clients' improved capability to process their emotions predicted better therapeutic outcomes. The current comparative study aimed to investigate whether emotional processing was related to therapeutic change in complicated grief. Method: We analyzed two contrasting cases (good or poor outcome) treated with grief constructivist therapy. In both cases we investigated the association of emotional processing (Experiencing Scale) to (1) therapeutic outcome (Inventory of Complicated Grief), and (2) change in the type of grief-related emotions (Emotions Episodes). Results: The session-by-session growth of clients' emotional processing and the change of grief-related emotions were qualitatively explored throughout both cases. Compared with the poor outcome case, the good outcome case achieved more improvement in the ability to process emotions. Such improvement occurred alongside a deeper change in the type of grief-related emotions aroused, from maladaptive to more adaptive responses. Conclusion: Our findings suggest that a higher emotional processing capability may be associated with the transformation of grief-related maladaptive emotions and with the improvement of complicated grief condition.